2008
DOI: 10.1016/j.freeradbiomed.2008.01.020
|View full text |Cite
|
Sign up to set email alerts
|

The complex role of iNOS in acutely rejecting cardiac transplants

Abstract: This review summarizes the evidence for a detrimental role of nitric oxide (NO) derived from inducible NO synthase (iNOS) and/or reactive nitrogen species such as peroxynitrite in acutelyrejecting cardiac transplants. In chronic cardiac transplant rejection, iNOS may have an opposing beneficial component. The purpose of this review is primarily to address issues related to acute rejection which is a recognized risk factor for chronic rejection. The evidence for a detrimental role is based upon strategies invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 146 publications
(195 reference statements)
0
7
0
Order By: Relevance
“…Similar effects were seen when using so called NO neutralizers [48,49]. An extensive review on the role of iNOS in acutely cardiac transplant rejection is given by Pieper and Roza [50].…”
Section: Heartmentioning
confidence: 72%
“…Similar effects were seen when using so called NO neutralizers [48,49]. An extensive review on the role of iNOS in acutely cardiac transplant rejection is given by Pieper and Roza [50].…”
Section: Heartmentioning
confidence: 72%
“…Blockade of NO production by iNOS inhibitors has been shown to prolong skin xenograft survival by down-regulation of the expressions of proinflammatory cytokines [41]. On the other hand, it is reported that NO derived from iNOS has a dual role in cardiac transplantation: detrimental in acute rejection and beneficial in chronic rejection [42]. Causal relationships between platonin-induced iNOS inhibition and attenuated skin graft rejection deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of an NO donor reverses these adverse effects on yolk sac vasculature 22 . Additionally, it has been reported that NO derived from iNOS plays a detrimental role in human disease 101 . Moreover, iNOS and eNOS are expressed during early embryonic vasculogenesis, and the alteration of NO expression induces yolk sac vasculopathy 22 .…”
Section: Molecular Intermediates and Signaling Pathways Contribute Tomentioning
confidence: 99%